A review of venous thromboembolism phenomena in COVID-19 patients (2020)
With the outbreak of the second peak of COVID-19 in many countries of the world, re-attention to the symptoms and complications of this disease has received much attention. One of the most important known complications of severe acute respiratory syndrome coronavirus 2 (SARSCoV-2) is the occurrence of venous thromboembolic (VTE) events, especially in critically ill patients and hospitalized in the intensive care unit. The pathology of this event is complex and multifactorial, but the main problem now is the timely diagnosis of these phenomena, which can reduce the mortality and morbidity of patients. Deterioration of clinical condition in patients with SARS-CoV-2 infection along with increased coagulation markers can increase clinical suspicion of VTE events. Imaging techniques, especially computed tomography pulmonary angiography, can well solve this puzzle and lead to timely treatment of these patients.